Evaluation of biocompatibility and bioactive potential of Well-Root PT by comparison with ProRoot MTA and Biodentine - Yong Kwon Chae; Ju Ri Ye; Ok Hyung Nam (Elsevier, 2024)
Background/purpose: Well-Root PT is a novel bioceramic material developed to overcome limitations of conventional calcium silicate cements. The purpose of this study was to assess the biocompatibility and bioactivity of a premixed putty-type cement, Well-Root PT. Materials and methods: Identical cylindrical samples were prepared from ProRoot MTA, Biodentine, and Well-Root PT. In vitro calcium weight volume and calcium ion release from the materials were evaluated with scanning electron microscopy and energy-dispersive spectroscopy and inductively coupled plasma-optical emission spectroscopy. An in vivo rat direct pulp capping model was implemented with the materials (n = 14 per material). The rats were sacrificed at 7 or 28 days. Hematoxylin and eosin and immunohistochemical analyses were performed. Results: In vitro calcium weight volume was 42.83 ± 8.82 % in ProRoot MTA, 47.05 ± 8.83 % in Biodentine, and 29.99 ± 4.94 % in Well-Root PT. Calcium ion releases from Well-Root PT after 7 and 28 days were similar with those from ProRoot MTA, but lower than those from Biodentine (P = 0.001 after 7 and 28 days equally). In an in vivo rat model, hematoxylin and eosin analysis showed no significant differences in inflammatory infiltration (P = 0.393) and hard tissue formation scores among the materials (P = 0.905). Also, both CD68 and DSPP expression showed similar results, with no significant differences among the materials (equally P = 0.874 for both markers). Conclusion: Within the limits of this study, Well-Root PT was comparable to ProRoot MTA and Biodentine in terms of biocompatibility and bioactivity.